HER 2 immunohistochemistry for breast cancer cell blocks can be used in the same way as that used for histological specimens. Issue 4 (22nd January 2016) - Nishimura, Rieko; Okamoto, Nami; Satou, Masakazu; Kojima, Kenta; Tanaka, Shinichi
Abstract : Background: Human epidermal growth factor receptor 2 (HER2) testing of samples from recurrent or metastatic breast cancer is recommended by the 2013 update of the American Society of Clinical Oncology/College of American Pathologists guidelines. Although cytological analysis can be applied to several types of metastatic lesions, the practical method for HER2 testing of cytological specimens is yet to be resolved. We conducted immunohistochemical (IHC) staining for HER2 in breast cancer cell blocks (CBs) and compared the results with those from the corresponding histological specimens. In cases of discrepancy between the two types of specimen, the bright‐field HER2 dual in situ hybridization (DISH) assay was performed. Methods: CBs were prepared from 54 surgically excised breast cancers. The cells were fixed in 10% buffered formalin and embedded in paraffin. A Ventana BenchMark ULTRA (Roche Diagnostics) with anti‐HER‐2/neu (4B5) rabbit monoclonal primary antibody and INFORM HER2/neu Dual ISH DNA Probe Cocktail was used for the assays. Results: Successful results were obtained in 52 of 54 CBs. Forty cases showed agreement between CBs and the histological specimens. No discrepancy was observed between the two types of specimens in cases where HER2 expression was positive. IHC results of CB in 12 discrepant cases were HER2 intermediate or negative. The DISH results of 11 of these cases were negative. Conclusion: IHC staining of HER2 for breast cancer CBs can be used in the same way as that used for histological specimens, although the number of equivocal cases in CBs is greater than that in histological specimens. Diagn. Cytopathol. 2016;44:274–279. © 2016 The Authors Diagnostic Cytopathology Published by Wiley Periodicals, Inc.